Prevalence of vegan/vegetarian diet and eating behavior among Saudi adults and its correlation with body mass index: A cross-sectional study - AL-Mohaithef, Mohammed (Frontiers in Nutrition, 2022)
Background:Globalization has steeredthe spread of vegetarianism around the world. Vegetarianism has achieved increasedacceptanceby different populations. Objective:The present study aims to assess vegetarian diet,and eating behaviorprevalence among Saudi adults and their association with demographics and body mass index. Method: Across-sectional study conducted on 1143 Saudi adults(418 (36.6%) males and 725(63.4%) females). An online survey questionnaire containing questions on demographics, type of diet, eating behavior and physical activitywas provided to participants for self-administration. Statistical analysis was performed to associate demographic and eating behavior variables with the type of dietusing Pearson’s Chi-square test and Spearman’spartial correlation testwas used to correlate BMI and eating behavior. Results:Prevalence of veganism was 4.7% (n=54/1143) and vegetarianism was 7.8% (89/1143). A significantly higher prevalence of vegan diet was observed in females than males (79.6%vs20.4%, p< 0.0001). A significantly higher proportion of participants on vegetarian diet selected ‘Always’ as response for eating breakfast, vegetables and fruits as well as for eating or drinking dairy foods,and for eating canned food than participants on non-vegetarian diet (p<0.0001). A significantly higher proportion of participants on vegan diet selected ‘Never’ for eating fast-food and fried food as well as for drinking fizzy or soft drinks (p<0.0001). A positive moderate correlation was found between BMI and eating fast-food and fried food (r(1140)=0.529, p<0.0001), drinking fizzy or soft drinks with meals (r(1140)=0.495, p=0.001), and eating canned food (r(1140)=0.510, p<0.0001). Conclusion:Our study shows that vegan and vegetarian diet have gained access into the lifestyle of Saudi adultswith a prevalence of 4.7% and 7.8%, respectively. Participants on vegetarian diet showed better lifestyle like higher physical activity level, higher consumption of fruits, vegetables, dairy products and low intake of fast-foods and fizzy beverages.